COT-05 A CASE OF NEPALESE IN JAPAN SUSPECTED OF NEUROCYSTICERCOSIS. (16th December 2019) - Mikai, Masataka; Matsuzaki, Ryo; Matsuura, Chie; Terazono, Sayaka; Ando, Shumpei; Harada, Masashi; Masuda, Hiroyuki; Kondo, Kosuke; Harada, Naoyuki; Sugo, Nobuo
Abstract: INTRODUCTION: Cystosis is the most common parasitic disease of the central nervous system. Especially in developing countries, it is one of the differential diagnosis of diseases that cause seizures. We report a case of a foreigner suspected of having neurocysticercosis. CASE: A 36-year-old Nepalese visiting Japan for 2 years. Two days ago, she lost consciousness for a few seconds and was transferred to our hospital complaint of convulsions for about 1 minute. Head Computed Tomography (CT) revealed a mass lesion with a ring enhancement effect of about 10 mm in the right frontal lobe, with edema around it. Magnetic Resonance Imaging (MRI) shows T1WI low signal, T2WI high signal, and diffusion-weighted image with a light high signal. The ring-shaped enhancement effect was exhibited. Whole body CT showed no obvious lesions and blood tumor markers were negative. Various infections were negative, and cerebrospinal fluid cytology and culture were negative. POSTOPERATIVE COURSE: From the surgical findings, brain abscesses such as cerebral tuberculoma were suspected, but various tests were negative. As a pathological result, the tumor had a capsule, and the inside showed necrotic tissue and fibrous granulation tissue reaction. There were no insects, and no obvious cells were identified by special staining. From the origin area, symptoms, and pathological findings, neurocysticercosis was most suspected. CONCLUSION: We experienced a case of suspected neurocysticercosis that was difficult to diagnose from images and pathological findings. In neurocysticercosis, when the worm body dies, contrast-enhanced MRI shows a ring-like enhancement effect, and it is accompanied by surrounding edema, which may require differentiation from brain tumors.